18F-NaF PET/CT identifies muscular and subcutaneous calcifications in both dermatomyositis- and systemic sclerosis-related calcinosis - Richardson, Carrie; Javadi, Mehrbod S.; Shah, Ami A.; Connolly, Caoilfhionn; Solnes, Lilja B.; Wigley, Fredrick M.; Hummers, Laura K.; Christopher-Stine, Lisa (Frontiers in Nuclear Medicine, 2025)
BackgroundCalcinosis is a morbid complication of dermatomyositis (DM) and systemic sclerosis (SSc) with no effective pharmacologic treatment or validated whole-body assessment modality. 18F-NaF PET/CT may help to quantify and characterize calcinosis.MethodsIn this pilot study, we enrolled three adults with DM and three with SSc, all with new calcinosis deposits. Each underwent 18F-NaF PET/CT and clinical examination with semi-quantitative scoring of calcinosis. We described the 18F-NaF PET/CT findings and compared these to CT imaging alone as well as to clinical examination.ResultsCalcinosis was noted on 18F-NaF PET/CT in the subcutaneous tissue in all patients and the muscle in three patients, including two with SSc. The average semi-quantitative score was 23.5 by 18F-NaF PET/CT and 20 by clinical exam. Wilcoxon signed rank test indicated greater scores by 18F-NaF PET/CT than by clinical exam (p = 0.0264). 18F-NaF uptake varied among calcinosis deposits and occurred without corresponding calcifications on CT.Conclusions18F-NaF PET/CT appears to be a sensitive method of detecting and characterizing calcinosis that provides both quantitative and qualitative data beyond what can be obtained by physical examination or CT alone. 18F-NaF uptake occurs in muscle in both SSc and DM, suggesting the possibility that myositis may be driving calcinosis in a subset of patients with SSc.